2009
DOI: 10.1021/jp811429e
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Metal Flux in Ligand Mixtures. 1. The Revisited Reaction Layer Approximation: Theory and Examples of Applications

Abstract: Understanding the physical chemical behaviors of each metal species in a solution containing a mixture of ligands is a prerequisite, e.g., for studying metal bioavailability or making predictions on dynamic risk assessment in ecotoxicology. For many years, the reaction layer concept has been used fruitfully due to its simplicity for understanding and making predictions on diffusion/reaction processes. Until now, it has been applied mainly to solutions containing one ligand. Here, we reconsider the fundamentals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(56 citation statements)
references
References 26 publications
1
55
0
Order By: Relevance
“…Previous works on voltammetric sensors under steady state conditions have shown [13][14][15] that the addition of labile ligands to the system tends to increase the lability degree of the more inert complexes, whereas the addition of inert ligands tends to decrease the lability degree of labile complexes. Buffle and co-workers 16,17 reported that the metal fux can be orders of magnitude diferent from what expected when the flux in the mixture is computed with the lability degrees of single ligand systems. We refer to "mixture effect" to indicate a change in the flux contribution of one metal-ligand complex due to the presence of other ligands also complexing the same metal when the SLS and the mixture share identical concentrations of free metal, ligand and complex.…”
Section: Introductionmentioning
confidence: 92%
“…Previous works on voltammetric sensors under steady state conditions have shown [13][14][15] that the addition of labile ligands to the system tends to increase the lability degree of the more inert complexes, whereas the addition of inert ligands tends to decrease the lability degree of labile complexes. Buffle and co-workers 16,17 reported that the metal fux can be orders of magnitude diferent from what expected when the flux in the mixture is computed with the lability degrees of single ligand systems. We refer to "mixture effect" to indicate a change in the flux contribution of one metal-ligand complex due to the presence of other ligands also complexing the same metal when the SLS and the mixture share identical concentrations of free metal, ligand and complex.…”
Section: Introductionmentioning
confidence: 92%
“…6). The main result of this figure is that there is also a good convergence of the theoretical results of the mixture system (at the rigorous level, by using eqn (10) or by using the reaction layer approximation, eqn (15) in ref. 16) with the experimental ones, while the theoretical results given by eqn (4) that neglect the interaction between the complexes diverge yielding lower flux values.…”
Section: 22mentioning
confidence: 75%
“…3,12 Despite mixtures of ligands corresponding to the most common situation in natural media, mixture effects have only recently been described. [13][14][15][16][17] By rigorous simulation, it has been shown that the increase of the concentration of one ligand decreases the lability degree of its complex in the mixture as in the case of a single ligand system, but also influences the lability degree of the other complexes. Thus, interactions of the complexes in a mixture can play unexpected and relevant roles in the metal availability.…”
Section: Introductionmentioning
confidence: 99%
“…More rigorously, the formulation of the reaction layer thickness should also take into account the mobility of the fully hydrated form and its mean free lifetime, 1/kd,i, (governed by the rate of release of water). The expression for such a generalised reaction layer thickness, i, defined by both the associative and dissociative terms for a given species i, is given by [52,53]:…”
Section: (De)hydration Kineticsmentioning
confidence: 99%